SPECTROSCOPIC CHARACTERIZATION AND UV-PROTECTIVE POTENTIAL OF ARCANGELISIA FLAVA EXTRACT - Tety Wahyuningsih Manurung; Rokiy Alfanaar; Mokhamat Ariefin; Marvin Horale Pasaribu; Eva Susanty Simaremare (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2025)
The increasing demand for natural UV-protective agents has led to the exploration of plant-based bioactive compounds. Yellow root (Arcangelisia flava) extract is traditionally used in medicine and contains flavonoids, alkaloids, and terpenoids with potential photoprotective properties. This study aimed to characterize the chemical composition of A. flava extract and evaluate its UV-absorbing properties using UV-Vis and FTIR spectroscopy. The extract was obtained through maceration with ethanol, followed by spectroscopic analysis. The UV-Vis spectrum (200–400 nm) revealed multiple absorption peaks, particularly at 270 nm, 292 nm, 306 nm, 340 nm, 354 nm, 360 nm, and 396 nm, indicating the presence of UV-absorbing compounds. FTIR analysis confirmed the presence of hydroxyl (-OH), carbonyl (C=O), and aromatic (C=C) functional groups, which are characteristic of flavonoids and other bioactive compounds. These findings suggest that A. flava extract has potential as a natural UV-protective agent. Further studies on compound isolation, fractionation, and photostability assessments are required to optimize its purity and effectiveness in sunscreen formulations.